SDGS5 (GENDER EQUALITY): PERFORMANCE OF WOMEN AS LEADERS OF ISLAMIC HIGHER EDUCATION INSTITUTIONS - Nur Wahyu Ningsih; Rieka Ramadhaniyah; Fitri Agustina; Saekarini Yuliachtri (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to examine the relationship between the SDGs report disclosure in Islamic higher education institutions and the performance of gender of rectors. The study used a quantitative approach as a disclosure index and nonparametric test to data analysis. The results show that there is no correlation between the SDGs report disclosure to performance of the gender of rectors and age university. Even though there is no influence of the gender of rector and age university on SDG report disclosure, the performance of female rectors is equally competitive with male rectors. This can be seen in several institutions led by female rectors that managed to enter the Webometrics PTKIN 2023 Ranking. A comprehensive understanding of the influence of gender and age university on rector performance and university commitment to the SDGs is crucial for fostering inclusive, equitable, and sustainable institutions. The findings of this research have important implications for policymakers, practitioners, and scholars in the field of higher education. Keywords: gender equality, higher education, SDGs report, women rector.